A strategy to defend the independence of Republic of Indonesia year 1948-1949: PEMERINTAH DARURAT REPUBLIK INDONESIA (PDRI) : Suatu Strategi Mempertahankan Kemerdekaan Republik Indonesia Tahun 1948-1949 - Rio Yenvan Permana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
One of the strategies of struggle to defend the independence of Indonesia is by forming an emergency Government of the Republic of Indonesia (PDRI). PDRI is a strategy of struggle by means of a transfer of power made by the Government of Indonesia Sjafruddin Prawiranegara to run the Government. The strategy transfer of power with the creation of PDRI is a step that is right for the Government of the Republic of Indonesia. This is because, with the fall of Yogyakarta and the capture of the leaders of the Republic of Indonesia. The method used in this study is the historical method consists of Heuristics, Criticism, Interpretation, and Historiography. The formation of the PDRI in 1948. Background of the formation of the PDRI in 1948. PDRI tactics in maintaining the independence of the Republic of Indonesia in 1948-1949. return of the mandate